Metaphysics, mathematics, and meaning - Salmon, Nathan U., 1951- (Clarendon Press ; Oxford University Press, 2005)
'Metaphysics, Mathematics and Meaning' brings together Nathan Salmon's influential papers on topics in the metaphysics of existence, non-existence and fiction. He includes a previously unpublished essay and helpful new introduction to orient the reader.
Keywords: Metaphysics.; Mathematics -- Philosophy.; Meaning (Philosophy); Metaphysics; Métaphysique.; Mathématiques -- Philosophie.; Signification (Philosophie); metaphysics.; PHILOSOPHY -- Metaphysics.; Mathematics -- Philosophy